2023
DOI: 10.1038/s41598-023-44996-6
|View full text |Cite
|
Sign up to set email alerts
|

Fault diagnosis of anti-friction bearings based on Bi-dimensional ensemble local mean decomposition and optimized dynamic least square support vector machine

Zhengqiang Xiong,
Chang Han,
Guorong Zhang

Abstract: In order to ensure the normal operation of rotating equipment, it is very important to quickly and efficiently diagnose the faults of anti-friction bearings. Hereto, fault diagnosis of anti-friction bearings based on Bi-dimensional ensemble local mean decomposition and optimized dynamic least square support vector machine (LSSVM) is presented in this paper. Bi-dimensional ensemble local mean decomposition, an extension of ensemble local mean decomposition from one-dimensional signal processing to Bi-dimensiona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Zhengqiang Xiong et al proposed a fault diagnosis method for friction-reducing bearings based on two-dimensional ensemble local mean decomposition and optimized dynamic least squares support vector machine (LSSVM). 8 . Shan Guan et al proposed a transformer fault diagnosis method based on TLR-ADASYN balance data set.…”
Section: Introductionmentioning
confidence: 99%
“…Zhengqiang Xiong et al proposed a fault diagnosis method for friction-reducing bearings based on two-dimensional ensemble local mean decomposition and optimized dynamic least squares support vector machine (LSSVM). 8 . Shan Guan et al proposed a transformer fault diagnosis method based on TLR-ADASYN balance data set.…”
Section: Introductionmentioning
confidence: 99%
“…The next (third) group of systems used to diagnose hydraulic systems are systems with elements of the so-called intelligent damage identification based on the use of machine learning and deep learning algorithms 11 13 . In the literature, there are many papers describing the use of such solutions in the diagnostics of hydraulic systems 14 16 .…”
Section: Introductionmentioning
confidence: 99%
“…However, EMD methods come with drawbacks like endpoint effects, underenvelopment, and modal aliasing. To address these issues, scholars have introduced enhanced versions of EMD methods, such as ensemble local mean decomposition (ELMD) [13,14], ensemble empirical modal decomposition (EEMD) [15,16], et al These improved methods have demonstrated success in enhancing the stability of EMD and overcoming challenges like mode aliasing. Nevertheless, the above methods also suffer from the disadvantage that the modal components of the decomposition lack physical significance.…”
Section: Introductionmentioning
confidence: 99%